PERAN CEO OVERCONFIDENCE DAN COMPANY PERFORMANCE TERHADAP RETURN SAHAM DIMODERASI DEVIDEND POLICY - Iswahyudi, Iswahyudi; Djaddang, Syahril; Suyanto, Suyanto; Darmansyah, Darmansyah (Pascasarjana Universitas Sultan Ageng Tirtayas, 2021)
AbstractThe most important of investors is to get high stock returns by considering the factors that influence it, because the case this research with the aim of analyzing and investigating the effect of Ceo Overconvidence and Company Performance on Stock Returns with a moderation of the Devidend Policy. This research approach uses quantitative research by analyzing and investigating the clausal relationship between variables. Based on 17 samples, it shows the results of simultaneous testing of independent variables such as SIM, SGM, DER, ROA and EPS have a significant effect on stock returns. Partially there are two independent variables DER and ROA which have a significant positive effect on stock returns and SIM that has a significant negative effect on stock returns, while the independent variables SGM and EPS have no significant effect on stock returns. Overall Dividend Policy cannot moderate the effect of the independent variables, namely DER, ROA, and EPS on stock returns.